Analysis of the fluctuation of the number of ISO 9001: 2015 certificates in the Republic of Croatia and assessment of satisfaction of business organisations leadership with the certificate - Petar Vušković (Naše gospodarstvo / Our Economy, 2020)
The ISO 9001:2015 certificate of quality is nowadays the most renowned quality standard in the world. Standardised quality has become an imperative competitive advantage on the market for all serious business organisations. The fluctuation of the number of certificates of quality indicates to what extent companies are willing to ensure the quality of their products and services to customers and clients, and how fast the domestic market is standardised and integrated into the global economy. This paper presents the results of two empirical studies. The first one focused on the analysis of the fluctuation in the number of ISO 9001:2015 certificates in the period from 2008 to 2018, while the second aimed to determine the satisfaction of leadership with the certificate. The study has shown that, during the observed period, the number of certificates of quality in Croatia fluctuated between - 18% and +22% annually. At the annual level, a certain number of companies lose their certificates or opt for decertification. For that reason, a study of the leadership's level of satisfaction with the ISO 9001:2015 certificate was conducted using a sample of 296 certified business organisations. The study has proven that the leadership showed a high level of satisfaction with the certificate of quality and that they appreciate business organisations with certificates of quality. It demonstrates that the quality management certification has a bright future regardless of the annual fluctuation of the number of certificates.
Keywords: M21; 330; certificate; standard; ISO 9001:2015 certificate; quality system; eadership; business organisations